Between preservation and recreation: Tamil traditions of commentary; proceedings of a workshop in honour of T. V. Gopal Iyer - Wilden, Eva (Collection Indologie, 2009)
The seed from which this book germinated was a workshop entitled "Between Preservation and Recreation: Tamil Traditions of Commentary in Pursuit of the Cankam Era", held in the Pondicherry Centre of the EFED from the 26th to 28th July 2006 in honour of the late and much lamented Pandit T.V. Gopal Iyer. The volume had been conceived as a felicitation volume of a particular kind, not simply a collective gift of essays loosely connected with his domain of study, but a concerted effort at improving our understanding of an area in which he had been a guide and landmark for almost all of us who met on that occasion: Tamil commentarial literature. A presentation of the life and work of T.V. Gopal Iyer, along with a voluminous bibliography, is followed by essays on different commentarial genres.
Includes bibliographical references
Keywords: Aufsatzsammlung; Konferenzschrift; Kommentar; Literatur; Tamil